Training police officers in the situational use of physical force based on a differentiated approach - Troyan E.I. (Theory and Practice of Physical Culture, 2023)
The results of the study revealed that training in the situational use of physical force will be effective, provided that situations of the use of physical force are differentiated according to two levels of complexity: universal and specialized.